Proses Penggantian Superheater Tube Pada Takuma Boiler N-900 R - Fathon'D, Ar Rasyid; Sutanto, Hadi; Hermanto, Tino (CV. IRA PUBLISHING, 2024)
This research aims to provide a detailed guideline for the replacement process of superheater tubes in the Takuma Boiler N-900 R. The superheater tube is a critical component in a boiler that increases the temperature of the steam exiting the boiler to achieve higher temperatures. Superheaters have been utilized since the early 20th century, coinciding with the initial use of steam engines. The research employed direct observation to analyze the causes of failure in the superheater tubes. The primary objective is to present the necessary processes and steps for replacing superheater tubes. The findings indicate that the primary cause of failure in the superheater tubes is overheating, necessitating their replacement. The replacement process involves several stages, including disassembling old superheater tubes, installing new ones, and testing hydrostatic and steam. The results of this replacement process show improved efficiency in the superheater and prevention of further failures in the superheater tubes.